The Relationship Between the Mandibular Bone Quality Assessed by Digital Panoramic Radiography and Serum Biological Parameters in Patients Planning Dental Implant Surgery - Cansu Köseoğlu Seçgin; Mehmet Özemre; Mediha Nur Nişancı Yılmaz; Kaan Orhan; Prof. Dr. Şule Bulut (Cumhuriyet University, 2020)
Abstract Objectives: The aim of this study was to evaluate the bone density of the implant site with panoramic radiomorphometric indices [mandibular cortical index (MCI), mental index (MI)] and to investigate the relationship between bone density and vitamin D, HDL, LDL. Materials and method: Forty patients with mandibular first molar or second molar tooth deficiency who underwent implant surgery planning were included. Blood samples and panoramic MCI and MI were used to evaluate mandibular bone density. Results: There was a significant weak positive correlation between MI and Vitamin D and LDL (r = 0.329, p = 0.038; r = 0.341, p = 0.031). Vitamin D, LDL and HDL measurements were not statistically different between MCI groups (p=0.100, p=0.119, p=0.840, respectively). Conclusions: Vitamin D may be important in addition to radiographic and clinical parameters, and patients should be evaluated in this respect. Further studies are needed to include more patients investigating the relationship between vitamin D and bone quality. Keywords: dental implants, bone remodeling, vitamin D, HDL cholesterol, LDL cholesterol Özet Amaç: Bu çalışmanın amacı, panoramik radyomorfometrik indeksler [mandibular kortikal indeks (MKI), mental indeks (MI)] kullanılarak implant bölgelerinde kemik densitesini değerlendirmek ve kemik densitesi ile D vitamini, HDL ve LDL arasındaki ilişkiyi incelemektir. Gereç ve Yöntemler: Çalışmaya mandibular birinci molar veya ikinci molar diş eksikliği olup implant cerrahisi planlanan 40 hasta dahil edilmiştir. Mandibular kemik densitesini değerlendirmek için kan örnekleri ve panoramik MKI ve MI kullanılmıştır. Bulgular: MI ile D vitamini ve LDL arasında anlamlı zayıf pozitif korelasyon bulunmuştur (r = 0.329, p = 0.038; r = 0.341, p = 0.031). MKI grupları arasında D vitamini, LDL ve HDL değerleri bakımından istatistiksel olarak fark bulunamamıştır (sırasıyla p = 0.100, p = 0.119, p = 0.840). Sonuçlar: D vitamini klinik ve radyolojik parametrelere ek olarak önemli bir faktör olabilmektedir ve hastalar bu açıdan değerlendirilmelidir. D vitamini ile kemik kalitesi arasındaki ilişkiyi araştıran daha çok sayıda hastanın dahil edildiği çalışmalara ihtiyaç vardır. Anahtar Kelimeler: diş implantları, kemiğin yeniden şekillendirilmesi, vitamin D, HDL kolesterol, LDL kolesterol